Exploring healthcare workers' experiences of managing patients returning to HIV care in Johannesburg, South Africa. Issue 1 (31st December 2022) - Bisnauth, Melanie A.; Davies, Natasha; Monareng, Sibongile; Struthers, Helen; McIntyre, James A.; Rees, Kate
ABSTRACT: Background: Retention of patients in HIV care is a critical barrier to reaching the UNAIDS 90–90-90 goals in South Africa. In January 2019, Anova Health Institute launched a campaign to encourage patients who had interrupted antiretroviral therapy to return to care. The Welcome Back campaign included training of health care workers and implementation of Médecins Sans Frontiers Welcome Services principles. Objective: The aim of this study was to explore the experiences of healthcare workers managing patients reinitiating antiretroviral therapy following training, including barriers and facilitators to implementation. Methods: Data were collected from six clinics. This study consisted of three components: 1) surveys; 2) semi-structured interviews and 3) reflexive feedback sessions. Each component covered staff attitudes and facility management of patients reinitiating antiretroviral therapy. A descriptive analysis was conducted of survey responses. A thematic approach was used to analyze interviews. Results: Thirty-six healthcare workers completed the survey and interview. Following analysis, feedback sessions were conducted with 99 healthcare workers. Twenty-two (61%) participants were lay counsellors. The majority of healthcare workers reported managing patients returning to care appropriately. However, barriers persisted: 9 (25%) responded that patients were sent to the back of the queue and that service providers continued to insist on transfer letters. Twenty-five (69%) responded they had seen/heard other healthcare workers act poorly towards returning patients after training. Many poor behaviours from healthcare workers stemmed from frustration with the clinical flow and their overburdened work environment. Many participants (78%) believed that the Welcome Back approach helped improve client-provider relationships. Conclusions: The Welcome Back approach supported healthcare workers to improve service provision for patients reinitiating antiretroviral therapy. Further support is needed to help providers consistently deliver services in line with the Welcome Back approach. Institutional level changes are required to implement patient-centred and trust-based models of care.